BREAK-EVEN POINT ANALYSIS AS A STRATEGIC TOOL FOR PROFIT PLANNING: EVIDENCE FROM UD TERASSUSU - Nava Nurlita; Khurin Wahyuni; Rohany Sukma (Universitas Tulungagung, 2024)
Profit planning is essential for micro, small, and medium enterprises (MSMEs) to maintain business sustainability and manage the relationship between sales, costs, and profitability. However, previous Break-Even Point (BEP) studies have predominantly examined larger firms or different business sectors, while empirical evidence concerning the application of BEP analysis to small beverage enterprises remains limited. This study aims to determine the Break-Even Point and evaluate its implications for profit planning at UD. Terasusu.mona12, a beverage MSME in Trenggalek, Indonesia. A quantitative descriptive case-study approach with an ex post facto design was employed using operational and financial data for December 2023. Data were collected through observation, interviews, and documentation. The analysis comprised contribution margin, contribution margin ratio, Break-Even Point, and Margin of Safety calculations. Based on the corrected cost calculations, total sales amounted to IDR 3,720,000, while total variable costs reached IDR 3,135,000 and fixed costs amounted to IDR 1,100,000. Consequently, the contribution margin was IDR 585,000, resulting in an operating loss of IDR 515,000. The weighted contribution margin ratio was 15.73%, producing a break-even sales level of approximately IDR 6.99 million, substantially above actual sales. The findings indicate that the company had not reached its break-even position during the study period. These results imply that BEP analysis can provide a practical basis for setting sales targets, controlling costs, and improving profit-planning decisions in MSMEs.